THE IMPACT OF EARLY DELHI SULTANATE'S MILITARY AND POLITICAL STRATEGIES ON MEDIEVAL INDIA - Dr. Khalid Bashir; Mr. Ishfaq Ahmad Mir (International Review of Practical Innovation, Technology and Green Energy (IRPITAGE), 2024)
ABSTRACT This research paper examines the political and military strategies of the early sultans of Delhi, namely Muhammad Ghori, Qutb-ud-din Aibak, and Iltutmish. The study explores their conquests and their impact on the political landscape of medieval India. The research draws on various primary and secondary sources to assess the military tactics, administrative policies, and socio-political conditions of the time. It analyses how these sultans sought to consolidate their power, expand their territories, and assert their authority over the diverse regions of India. The study also evaluates the long-term consequences of these conquests on the subsequent history of the subcontinent, including the emergence of a new ruling elite, the spread of Islam, and the fragmentation of political power. Overall, this paper offers insights into the complex processes of state-building and imperial expansion in medieval India and sheds light on the enduring legacies of the early sultans of Delhi.